Inventory Control of Coffee Raw Materials Using The Economic Order Quantity (EOQ) Method - Yaning Tri Hapsari; Theofilus Bayu Dwinugroho; Anton Anton (Institut Teknologi Dirgantara Adisutjipto, 2026)
Management of raw material supplies at the Kopi Merapi Babadan is still carried out conventionally. The purchase of raw materials made by the Kopi Merapi Babadan did not have a plan and was based on estimates only. This often causes a mismatch in the existing raw material inventory with the number of raw materials to be processed in the production process, causing the costs incurred to purchase raw materials inappropriately. The EOQ method is a method that is often used in supply chain concepts. Applying the Economic Order Quantity (EOQ) method can provide an estimate of the raw material requirements that will be used in the production process to balance the expenditure of raw materials and the products produced. This research aims to control the supply of coffee beans using the EOQ method. The data collected is in the form of data on the amount of raw materials needed, the number of orders for raw materials, ordering costs, and storage costs. The savings that the Company can make by implementing EOQ for optimal orders are IDR 550.000,- or 31,34%. The company saves IDR 294,020 (24.50%) by coordinating with suppliers compared to using EOQ without coordination. The company can save 48.23% or IDR 844,020 if it uses EOQ with supplier coordination, compared to the company's actual conditions.